High-purity SWCNT additive for improving the performance of lithium-ion batteries

KR103013086B1Active Publication Date: 2026-09-01YAZAKI CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020227015089
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-04
Filing Date
2020-09-25
Publication Date
2026-09-01
Estimated Expiration
2040-09-25

Smart Images

  • Figure 112022047612491-PCT00007_ABST
    Figure 112022047612491-PCT00007_ABST
Patent Text Reader

Abstract

The present invention relates to a lithium-ion battery cell having a cathode comprising about 1-5 wt% of single-walled carbon nanotubes (SWCNT) as an active material and a conductive additive, wherein the SWCNT has an inorganic impurity content of less than 5 wt%. The LiB cathode of the present invention improves performance characteristics such as higher capacity, lower cell resistance, and greater capacity retention through cycling of a fully assembled cell compared to a LiB cell using only a conventional conductive carbon additive in the cathode.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to the use of purified single-walled carbon nanotubes (SWCNTs) as a conductive additive in a lithium-ion battery cathode for significantly improved performance characteristics of a fully assembled cell compared to a lithium-ion battery cell using only conventional conductive carbon additives such as carbon black in the cathode. Background Technology

[0002] Lithium-ion batteries (LiBs) are commonly used in consumer electronics and are attractive for use in hybrid gas-electric and all-electric vehicles. However, improvements in battery performance are required for widespread vehicle applications. In particular, increased energy density, power density, lighter weight, and better reliability are desirable. Thinner and / or lighter electrode materials with lower electrical resistance, more efficient ion transport capabilities, and sufficient mechanical strength for battery use are particularly attractive.

[0003] There is a growing demand for the development of battery chemistry that offers improved performance metrics compared to those currently achieved with LiB technology. The US DOE has set performance targets for LiB cells, such as a capacity of 350 Wh / kg (750 Wh / L), continuous operation for at least 1,000 cycles, and an expected lifespan of over 10 years. At the battery module and pack levels, targets are equally high: rapid charging (to 80% charge) within 15 to 30 minutes, and battery pack costs reduced to $125 to $80 per kWh. To achieve these ambitious goals, new battery chemistry, particularly the cathode formulation of these energy storage devices, is critical. Conventional LiB configurations consist of a cathode with a Li metal oxide as the active material (e.g., Li-NiMnCo-Oxide (NMC), Li-NiCoAl-Oxide (NCA), Li-Fe-Phosphate (LFP), Li-Cobalt-Oxide (LCO), Li-Manganese-Oxide (LMO)). These oxides are in the form of fine particles and must contain polymer binders, such as polyvinylidene difluoride (PVDF), to form a cohesive electrode coating on the current collector. PVDF binders are insulating. Additionally, Li metal oxides are resistive. Therefore, conductive additives, such as carbon black, are included in the cathode formulation to lower the overall electrode resistance. All of these components are mixed with suitable solvents, such as N-methyl-2-pyrrolidone (NMP), isopropanol (IPA), or water, and processed into a slurry for coating application. While the inclusion of binders and conductive additives is necessary, these components do not contribute to the capacity of the LiB cell. In fact, common practice is to incorporate these inactive additives at the lowest practical level to maximize the concentration of the active material. The result of this customized cathode formulation is increased energy density.

[0004] Carbon nanotubes (CNTs) are mainly sp 2It is a one-dimensional cylindrical graphite nanostructure composed of hybrid carbon atoms. CNTs are classified according to the number of cylindrical graphite sheets or "walls" that make up the individual nanotube structure. Nanotubes with a single wall are called single-wall carbon nanotubes (SWCNTs) and are distinguished from nanotubes with two or more walls, known as multi-wall carbon nanotubes (MWCNTs). MWCNTs with two walls are also called double-wall carbon nanotubes (DWCNTs). Both types of CNTs, namely SWCNTs and MWCNTs, have nanometer-sized diameters and micron-sized lengths, offering high surface-to-volume ratios and high aspect ratio characteristics. Since the typical diameter of an individual SWCNT is 5 to 50 times smaller than that of an individual MWCNT, SWCNTs have a much higher aspect ratio than MWCNTs.

[0005] To enable next-generation advanced lithium-ion batteries, new materials capable of functioning as beneficial additives in the cathode of LiB cells are required to improve performance metrics such as higher capacity, lower cell resistance, higher charge and discharge rate capabilities, and greater capacity retention over cycling. Brief explanation of the drawing

[0006] Figure 1 shows images of slot die roll-to-roll coating of a LiB cathode material containing SWCNT as a conductive additive on an Al foil: (A) coating for a LiB energy cell, (B) coating for a LiB power cell. Figure 2 is a set of two charts illustrating the performance gain in a Type 18650 LiB energy cell containing refined SWCNT as a conductive additive compared to a LiB cell with a conventional carbon black conductive additive (Super-P® or "SP", Imerys Graphite & Carbon, Terrebonne, Quebec, Canada). Figure 3 is a chart comparing the lifecycle capacity of Type 18650 LiB energy cells containing 6 wt% standard carbon black (SP) conductive additive (labeled as Control), 1 wt% refined SWCNT + 1 wt% carbon black (SP), and refined SWCNT. Figure 4 is a set of two charts showing the charge and discharge capacity performance gains achieved in a power cell when using SWCNT purified with a conductive additive at different concentrations compared to a conventional carbon black additive (standard cell of 6 wt% SP). Figure 5 is a chart showing the difference in discharge capacity performance gain achieved in a power cell when using SWCNT (CNT) or purified SWCNT accepted as a conductive additive compared to a conventional carbon black (SP) additive. Figure 6 is a chart showing the reduction in cell impedance achieved in a power cell when using SWCNT purified with a conductive additive at different concentrations compared to a conventional carbon black additive (standard cell of 6 wt% SP). Figure 7 is a set of two charts showing improved discharge rate performance at increasing discharge current of a LiB power cell containing (B) purified SWCNT as a conductive additive compared to (A) a conventional carbon black additive (6 wt% SP). Figure 8 is a chart showing the improved discharge rate performance at a discharge current of 20A of a LiB power cell containing SWCNT purified with a conductive additive at 2wt% and 3wt% compared to a cell containing a carbon black additive (standard cell with 6wt% SP). Figure 9 is a chart comparing the discharge rate performance at a discharge current of 20A of a LiB power cell containing SWCNT purified with a conductive additive at 2wt% versus an incorporated SWCNT additive at 2wt%. Figure 10 is a chart showing the improved life cycle performance (normalized discharge capacity) of a representative LiB power cell containing 2 wt% of purified SWCNT as a conductive additive compared to a cell containing carbon black additive (standard cell 6 wt%). Figure 11 is a chart showing the superior early life cycle performance (normalized discharge capacity) of a LiB power cell containing 2 wt% purified SWCNT + 2 wt% carbon black (SP) as a conductive additive compared to a cell containing 2 wt% incorporated SWCNT + 2 wt% carbon black (SP) as a conductive additive. Figure 12 is a set of charts showing the improved performance of LiB parameters of charge capacity (top), discharge capacity (middle), and cell impedance (bottom) when SWCNT is included as a conductive additive to reduce or completely replace carbon black content. It represents the best performance in each category of energy cells or power cells. Figure 13 is a chart showing the superior early life cycle performance (normalized discharge capacity) of a LiB power cell containing 2 wt% highly purified SWCNT as a conductive additive compared to a cell containing 2 wt% purified SWCNT or accepted SWCNT as a conductive additive, each having 2 wt% carbon black (SP). Figure 14 is a chart comparing the discharge rate performance at a discharge current of 20A for LiB power cells containing various grades of SWCNT as a conductive additive at 2wt%: accepted, purified, and highly purified SWCNT (each containing 2wt% SP). FIG. 15 is a chart showing the lifecycle performance (normalized discharge capacity) of LiB power cells containing accepted MWCNTs for cells containing purified or highly purified SWCNTs accepted as a conductive additive at 2 wt% (each having 2 wt% SP), or for cells not containing CNTs (6 wt% SP). Figure 16 is a chart comparing the discharge rate performance at a discharge current of 20A for LiB power cells containing MWCNTs for cells containing various grades of SWCNTs as conductive additives at 2wt% (each having 2wt% SP) or for cells not containing CNTs (6wt% SP). Specific details for implementing the invention

[0007] The inventors have discovered that the use of high-purity and well-dispersed conductive carbon nanotubes, particularly single-walled carbon nanotubes (SWCNTs), as conductive additive materials for the cathode formulation of Li-ion batteries improves the performance characteristics of fully assembled LiB cells. Unlike conventional carbon black particles, the high aspect ratio of carbon nanotubes provides good contact between active metal oxides and allows conductive penetration at a lower integration level. Control of cathode morphology and porosity is essential. Low porosity results in a smaller surface area and a higher diffusion coefficient, which shortens the response time (Chang Kyoo Park et al , Bull. Korean Chem. Soc. 2011, Vol. 32, No. 3, p. 836-840). To achieve the desired performance improvement, the inventors have specified that the SWCNT must be of high purity containing less than 5 wt% inorganic impurities and 400 to about 1300 m 2 / g, preferably 800 to about 1300 m 2 It was found that they must have a BET specific surface area of ​​1 / g and be highly graphitized with minimal tube defects (verified by a Raman G / D ratio > 20 when measured using a laser with a wavelength of 532 nm). Integrating conductive SWCNTs with these specific criteria into the cathode formulation of LiB cells provides the necessary performance gains of increased capacity, increased rate performance, increased cycle life, and reduced impedance to enable next-generation battery systems that meet established target criteria.

[0008] The inventors have discovered that the use of SWCNTs rather than MWCNTs as a conductive additive material for the cathode formulation of Li-ion batteries improves the performance characteristics of fully assembled LiB cells. The advantage of using SWCNTs instead of MWCNTs as a conductive additive material in the cathode formulation of LiBs is due to the higher aspect ratio and higher surface area provided by SWCNTs. SWCNTs generally have an aspect ratio 5 to 50 times higher than MWCNTs. SWCNTs are generally hundreds to thousands of m² larger than MWCNTs. 2 They have a surface area greater than 1 / g. This combination of a higher aspect ratio and a higher surface area provided by SWCNTs makes these nanotubes more attractive than MWCNTs for use in the present invention as conductive carbon additives.

[0009] A LiB cell typically comprises a carbon-based anode, a cathode, and an electrolyte containing a lithium salt in an organic solvent.

[0010] The present invention relates to a LiB cell having a cathode comprising about 1-5 wt% of single-walled carbon nanotubes (SWCNT) as an active material and a conductive additive, wherein the SWCNT has an inorganic impurity content of less than 5 wt% or less than 4.5 wt%.

[0011] As used in this application, "about" indicates ± 10% of the cited value.

[0012] Unless otherwise specified, % in this application means weight (wt)%.

[0013] The active material of the cathode of the LiB of the present invention typically contains a material selected from the group consisting of: Li-NiMnCo-Oxide (NMC), Li-NiCoAl-Oxide (NCA), Li-Fe-Phosphate (LFP), Li-Cobalt-Oxide (LCO), Li-Manganese-Oxide (LMO), and any combination thereof. The LiB cathode of the present invention typically contains 91-99 weight%, preferably 92-98 or 92-97 weight% of the active material.

[0014] The cathode of the LiB of the present invention may include a polymer binder. For example, polyvinylidene difluoride (PVDF) may be used as a binder in the cathode. The binder may be present in an amount of 0.5-8 wt%, preferably 1-6 wt%, and more preferably 1-2 wt% in the LiB cathode.

[0015] In one embodiment, the LiB cathode includes a polymer binder.

[0016] In one embodiment, the LiB cathode does not contain a polymer binder. In this embodiment, carbon nanotubes in the LiB cathode composition act as a binder that binds any other components, such as active oxide particles and carbon black, together. As described above, the polymer binder does not contribute to the capacity of the LiB cell, and it is advantageous to minimize or completely eliminate the amount of polymer binder in the cathode composition.

[0017] In one embodiment, the SWCNT is purified and contains inorganic impurities of ≤ 5%, ≤ 4.5%, ≤ 4%, ≤ 3%, ≤ 2%, or ≤ 1 weight%. By comparison, commercial SWCNTs generally contain inorganic impurities of 10% or more (e.g., 10-25%) by weight, including iron (Fe), nickel (Ni), silicon (Si), and / or other metals. These metal impurities are generally present as residues of the manufacturing process.

[0018] In one embodiment, the cathode comprises about 0.5 to 4.5 wt% SWCNT. In another embodiment, the cathode comprises about 1 to 4.5 wt% or 1.5 to 4.5 wt%, or 2 to 4 wt% SWCNT. For example, the cathode comprises about 1, 2, 3, or 4 wt% SWCNT.

[0019] In one embodiment, the cathode includes SWCNT as the sole conductive additive.

[0020] In one embodiment, the cathode contains SWCNT as a conductive additive and does not contain a significant amount of carbon black. For example, the cathode does not contain more than 0.1 weight% of carbon black or does not contain any carbon black.

[0021] In another embodiment, the cathode further comprises a second conductive additive, such as carbon black. Acetylene black, a type of carbon black with high crystallinity, can be used as the second conductive additive.

[0022] In one embodiment, the ratio of two conductive additive SWCNTs to carbon black at the cathode may be in the range of 1:3 to 3:1; preferably in the range of 1:2 to 2:1, more preferably about 1:1.

[0023] The amount of conductive carbon additive in the cathode varies depending on the requirements of the application in which the battery is used. Power cells have a higher conductive carbon content (4-10 wt%) and a lower active material content to lower cell resistance. However, this comes at the cost of losing storage capacity. Energy cells have a lower conductive carbon content (2-4 wt%) and a higher active material content to achieve high storage capacity. However, this comes at the cost of losing rate capability.

[0024] In one embodiment, the combined content of SWCNT and carbon black is 1% to 8% by weight, preferably 2% to 6% by weight, in the cathode.

[0025] In one embodiment, the cell is a power cell, and the combined content of SWCNT and carbon black in the cathode is 4 wt% to 10 wt%, preferably 4 wt% to 8 wt%, more preferably 4 wt% to 6 wt%.

[0026] In one embodiment, the cell is an energy cell, and the combined content of SWCNT and carbon black in the cathode is 2% to 4% by weight, preferably 2% to 3% by weight, more preferably about 2% by weight.

[0027] For example, a LiB power cell cathode may contain about 92 wt% NMC, about 2 wt% PVDF, about 3 wt% SWCNT, and about 3 wt% carbon black.

[0028] For example, a LiB power cell cathode may contain about 94 wt% NMC, about 2 wt% PVDF, about 2 wt% SWCNT, and about 2 wt% carbon black.

[0029] For example, a LiB power cell cathode may contain about 94 wt% NMC, about 2 wt% PVDF, and about 4 wt% SWCNT. In one embodiment, this cathode contains less than 0.1 wt% carbon black. In another embodiment, this cathode does not contain any carbon black.

[0030] For example, a LiB energy cell cathode may contain about 96 wt% NMC, about 2 wt% PVDF, and about 2 wt% SWCNT. In one embodiment, this cathode contains less than 0.1 wt% carbon black. In another embodiment, this cathode does not contain any carbon black.

[0031] For example, a LiB energy cell cathode may contain about 96 wt% NMC, about 2 wt% PVDF, about 1 wt% SWCNT, and about 1 wt% carbon black.

[0032] In one embodiment, the thickness of the cathode is at least 100 μm.

[0033] The present invention utilizes purified SWCNTs to supplement or replace carbon black materials as a conductive additive in the cathode of a LiB cell. Because SWCNTs have a smaller diameter, their aspect ratio is significantly higher than that of multi-walled carbon nanotubes (MWCNTs). Consequently, one of the challenges faced when processing high aspect ratio SWCNTs in solution is to overcome substantial van der Waals interactions to achieve stable dispersion of the SWCNTs. A common approach is to use appropriate dispersants or surfactants to minimize agglomeration and re-bundling of the nanotubes after processing in solution. However, the presence of these agents negatively affects intrinsic CNT properties, such as high electronic conductivity, and adds additional post-processing time and cost to remove the dispersants from the processed CNTs.

[0034] The present invention describes treating purified SWCNTs with a high aspect ratio into a stable dispersion without using a dispersant or surfactant. Aggregates and large bundles of SWCNTs are sufficiently reduced in size by high-shear treatment and remain suspended and dispersed in a carrier solvent for a long period without separation or precipitation. The mechanically treated SWCNT dispersion is stable in that no clumping or precipitation of the dispersed nanotubes is observed even after being left at room temperature for at least 24 hours or for at least several weeks.

[0035] Since dispersants or surfactants are not used to prepare the SWCNT dispersion, the cathode material composition of the present invention is completely free of such substances. If present in the cathode material, these substances can have a detrimental effect on the cathode performance of the assembled LiB cell. By removing these substances during the SWCNT dispersion process, they are not present in the cathode material, and therefore, such performance loss does not occur when the cathode material is used in the assembled LiB cell.

[0036] The effect of treating SWCNTs as a stable dispersion according to the present invention is demonstrated in the superior cycling and rate performance of an assembled LiB cell having SWCNTs treated as an additive in the cathode compared to a cell containing MWCNTs as an additive.

[0037] In the present invention, the SWCNT may be a metallic SWCNT, a semiconductor SWCNT, or preferably a mixture of metallic and semiconductor SWCNTs. Taken together, this mixture of high aspect ratio, high-purity metallic and semiconductor SWCNTs possesses relatively high electrical conductivity. Furthermore, the SWCNT is purified to such an extent that the content of detectable metals and other impurities is less than 5 wt% when measured using a laser with a wavelength of 532 nm, and the Raman G / D integrated peak area ratio is at least 20, preferably >30, >40, >50, or >60. The purified SWCNT is 400 m 2 / g to about 1300m 2 / g, preferably 800m 2 / g to about 1300m 2 / g, more preferably 900m 2 / g to 1300m 2 / g, or 1000 to about 1300m 2 / g, or 1100 to about 1300m 2 It has a BET specific surface area between / g.

[0038] Using refined SWCNTs with a high aspect ratio generally reduces the total conductive additive content of the cathode to lower the overall level compared to using only carbon black, especially in the case of LiB power cells. This feature allows for a higher proportion of active material, which not only increases capacity but also improves cell capacity utilization compared to standard LiB cells. This design allows for increased capacity (energy density) at a given impedance and power density. In contrast, in conventional LiB power cell structures, capacity (energy density) decreases as the ratio of conductive carbon to active material increases, which was possible to achieve low impedance and high power density.

[0039] The resulting performance gains achieved by the LiB cell of the present invention containing SWCNT additives are significant in terms of increased capacity, lower impedance, improved capacity retention at high discharge rates, and superior lifecycle characteristics compared to the performance of a LiB cell with a standard carbon black conductive additive. Furthermore, these numerous and substantial performance improvements are greatly enhanced by incorporating purified SWCNTs into the LiB electrode. Similar performance gains could be achieved using MWCNTs as conductive additives. Commercially available SWCNTs may contain 10 to 25 wt% inorganic impurities and varying amounts of amorphous carbon. Incorporating the accepted SWCNTs into the LiB cathode in the same amount as purified SWCNTs results in a LiB cell with weakened performance improvements. Compared to a LiB cell with the same amount of purified SWCNTs containing less than 5 wt% metal impurities, it exhibits a 4% smaller capacity increase, 10% lower capacity at high discharge rates, and faster capacity fade with cycling (8% capacity fade after 150 cycles vs. 5% for purified SWCNTs). Incorporating highly purified SWCNTs with less than 1 wt% metal impurities as a conductive additive to the cathode in the same amount as purified SWCNTs resulted in a further improvement in LiB performance compared to that achieved with purified SWCNTs.

[0040] The present invention is further illustrated by the following examples, which should not be construed as limiting the invention to the specific procedures and products described herein.

[0041] Examples

[0042] Example 1. Preparation of SWCNT-NMP dispersion

[0043] A dispersion of SWCNTs in N-methyl-2-pyrrolidone (NMP) was prepared using accepted commercial SWCNTs (~14 wt%, generally containing 10-25 wt% inorganic impurities), purified SWCNTs (< 5 wt%, generally containing 2-4 wt% inorganic impurities), and highly purified SWCNTs (≤ 1 wt% inorganic impurities).

[0044] 3 g of each SWCNT type was combined with 1 L of NMP and treated by crude ultrasonication using impeller mixing for 1 hour. After this pre-mixing treatment, the SWCNTs were dispersed via a high-shear process. The typical viscosity of the resulting SWCNT-NMP dispersion was 0.1 s⁻¹. -1 The shear rate ranged from 80,000 to 90,000 cP. The three resulting dispersions, each with a different SWCNT type, were stable at room temperature for at least 24 hours without separation or precipitation.

[0045] Example 2. Integration into a cathode formulation

[0046] Formulation A: Refined SWCNT Exclusive (Carbon Black-Free)

[0047] In Formulation A, purified SWCNT (< 5 wt% inorganic impurities) was used as a conductive additive to completely replace the traditional carbon black additive, and was used at 2 wt% and 4 wt% for the LiB energy cell and power cell, respectively. The purified SWCNT-NMP dispersion prepared in Example 1 was used with Ni, referred to as the commercial Li metal oxide active material - NMC111. 0.33 Mn 0.33Co 0.33 It was incorporated into a cathode formulation mixture containing [the substance]. Additionally, a 2 wt% PVDF binder dissolved in NMP solvent was used in the formulation mixture. The entire mixture was introduced into a 60 L mixer equipped with both high-shear and oily mixing capabilities and processed overnight under vacuum. The viscosity of the resulting processed cathode slurry mixture, having a solid content of 19 wt%, was 26,000 cP when measured using a Brookfield RV instrument with spindle #4 at 2 rpm.

[0048] Formulation B: Refined SWCNT + Carbon Black (SP)

[0049] In Formulation B, purified SWCNTs were used as a conductive additive to partially replace and reduce the amount of conventional carbon black additives. Purified SWCNTs (< 5 wt% inorganic impurities) were incorporated in varying amounts: 1 wt% SWCNT + 1 wt% carbon black (Super-P® or "SP", Imerys Graphite & Carbon, Terrebonne, Quebec, Canada) for LiB energy cells, and 2 wt% and 3 wt% SWCNTs with 2 wt% and 3 wt% carbon black, respectively, for LiB power cells. Thus, in all cases, carbon black was present in each formulation, but in reduced amounts compared to standard LiB cells, which generally contain between 4 and 10 wt% carbon black for LiB power cells. Additionally, a 2 wt% PVDF binder dissolved in NMP solvent was used in the formulation mixture.

[0050] Formulation C: Accepted SWCNT + Carbon Black (SP)

[0051] In Formulation C, accepted commercial SWCNTs (approx. 14 wt% inorganic impurities) were used as a conductive additive to partially replace and reduce the amount of conventional carbon black additive. Accepted commercial SWCNTs (approx. 14 wt% inorganic impurities) were included in an amount of 2 wt% SWCNT + 2 wt% carbon black for LiB power cells. This formulation is identical to the above-mentioned Formulation B, which contains 2 wt% purified SWCNT + 2 wt% carbon black, and was prepared to compare the effect of SWCNT purity on the performance characteristics of LiB cells. Additionally, a 2 wt% PVDF binder dissolved in NMP solvent was used in the formulation mixture.

[0052] Formulation D: Standard LiB Cell: Carbon Black Control (SP)

[0053] A standard LiB energy cell was formulated to contain 2 wt% carbon black, and a standard LiB power cell was formulated to contain 6 wt% carbon black. These served as respective control cells. Additionally, a 2 wt% PVDF binder dissolved in NMP solvent was used in the formulation mixture.

[0054] Table 1 summarizes all of the above-mentioned manufactured formulations A to D and their compositions.

[0055] Table 1 Cathode Formulation. formulation Li active material Purified SWCNT wt% Accepted SWCNT wt% Carbon Black wt% Binder wt% Active substance wt% Power or Energy Cell (P / E) A NMC 111 4 0 0 2 94 P NMC 111 2 0 0 2 96 E B NMC 111 3 0 3 2 92 P NMC 111 2 0 2 2 94 P NMC 111 1 0 1 2 96 E C NMC 111 0 2 2 2 94 P D NMC 111 0 0 6 2 92 P NMC 111 0 0 2 2 96 E

[0056] Table 2 shows the difference in inorganic (metal) impurity content in one batch of accepted commercial SWCNT, purified SWCNT, and highly purified SWCNT, respectively, used as conductive additives in LiB cells.

[0057] Table 2 Comparison of inorganic impurity content among three grades of SWCNT. impurities Accepted SWCNT (%) Purified SWCNT (%) Highly purified SWCNT(%) Analysis method Fe 10.51 1.90 0.35 ICP Ni 0.043 0.009 0.009 ICP-MS Si 0.020 0.010 0.010 ICP-MS

[0058] Example 3. Coating of cathode formulation on Al foil

[0059] Freshly processed cathode formulations A to D prepared in Example 2 were coated on both sides of a roll of battery-grade Al foil (thickness 15 μm) via slot-die coating using a Lab Coater and dryer (Frontier Industrial Tech Inc.). The wet coating was subsequently dried in an 8-zone convection oven drying chamber of the slot die coater, with the temperature passing through the zones being 93.3 to 127 °C.

[0060] For the energy cell, the average dry electrode thickness of the results was approximately 300 μm, which decreased to approximately 170 μm after calendering. The coating weight per surface was 3 g / cm². 3 Approximately 25 mg / cm² corresponding to a higher density 2 was. Fig. 1(A) It shows a representative wet cathode coating for Al foil for energy cells.

[0061] For the power cell, the resulting dry electrode thickness was approximately 195 μm, which decreased to about 98 μm after calendering. The coating weight per surface was 3 g / cm². 3 Approximately 13 mg / cm² corresponding to a higher density 2 was. Fig. 1(B) It shows a typical wet cathode coating for power cells.

[0062] Example 4. Type 18650 cell assembly

[0063] For the assembly of the entire cell, LiB cathodes containing the SWCNT additive prepared in Example 3 were slit and each combined with a standard graphite insert anode composed of BTR 918 graphite powder (BTR New Energy Materials, China), carbon black conductive additive (Super P®), carboxymethylcellulose (CMC) gelling agent, and styrene-butadiene rubber (SBR) as a binder. This anode formulation was also slot-die coated onto battery-grade Cu foil to create an anode electrode. Each cathode was paired with an anode and assembled into a Type 18650 cell filled with LiPF6. Using each of the aforementioned prepared cathodes, Type 18650 cells were assembled to operate and test as a complete LiB energy cell and power cell.

[0064] Example 5. Performance comparison of purified SWCNT versus carbon black as a conductive additive in a LiB energy cell

[0065] The electric capacity of a LiB is the total ampere-hour (Amp-hour) available when the battery is discharged from a 100% charge state to a cutoff voltage at a specific discharge current (designated as the C-rate). Discharge capacity is calculated by multiplying the discharge current (amperes) by the discharge time (hours). In this embodiment, all LiB cells were discharged from an initial voltage of 4.2V to a cutoff voltage of 3.0V.

[0066] Fig. 2 It shows a comparison of performance data between a standard LiB energy cell containing 96 wt% NMC, 2 wt% binder, and 2 wt% carbon black in the cathode and the LiB energy cell of the present invention containing 96 wt% NMC, 2 wt% binder, and 2 wt% SWCNT in the cathode.

[0067] It was observed that replacing the 2wt% carbon black additive with 2wt% SWCNT increased cell capacity by 5% and reduced cell ESR by 6%.

[0068] Changes in electrode formulation generally result in changes corresponding to a single performance criterion in LiB cells. The uniqueness of this case lay in achieving simultaneous performance gains of both increased capacity and reduced impedance from the same cathode formulation containing 2 wt% SWCNT. Including 1 wt% SWCNT and carbon black resulted in a 4.5% reduction in cell ESR compared to a standard cell containing 2 wt% carbon black.

[0069] The increase in cell capacity resulting from the use of 2 wt% purified SWCNT as a conductive additive was observed initially and persisted throughout the life cycle, as shown in Fig. 3. A LiB cell containing 1 wt% SWCNT + 1 wt% carbon black exhibited an initial cell discharge capacity similar to that of a standard cell using 2 wt% carbon black, and demonstrated better retention of cell capacity over cycling compared to the standard cell. A cell containing 6 wt% carbon black showed a sharp decrease in capacitance within the first few cycles, followed by a gradual decrease in capacitance. A less steep drop in capacitance was observed within the first few cycles in a cell containing 1 wt% carbon black and 1 wt% SWCNT. Conversely, in a cell containing 2 wt% SWCNT but without carbon black, no sharp drop in capacitance was observed within the first few cycles. Instead, only a gradual decrease in capacitance was observed.

[0070] Example 6. Performance comparison of purified SWCNT versus carbon black as a conductive additive in a LiB power cell

[0071] A LiB power cell was assembled with a cathode containing purified SWCNT as a conductive additive. As shown in Fig. 4, the LiB power cell of the present invention, having a cathode containing 2 wt% purified SWCNT + 2 wt% carbon black in an optimized amount, exhibited a charge capacity gain of approximately 9.6% and a discharge capacity gain of 6.7% compared to a standard LiB power cell having a cathode containing 6 wt% carbon black. Smaller increases in capacity and discharge capacity were observed for amounts of 3 wt% purified SWCNT + 3 wt% carbon black in the cathode and 4 wt% purified SWCNT without carbon black in the cathode. The results demonstrate that adding purified SWCNT to the cathode is advantageous, and that maximum gains in both charge and discharge capacities can be obtained by optimizing the total content and ratio of SWCNT and carbon black.

[0072] Adding 2 wt% of incorporated SWCNT + 2 wt% carbon black to the cathode of a LiB power cell provided a gain in discharge capacity compared to a standard LiB cell with only carbon black, as shown in Figure 5. However, the capacity increase was only 2.4% compared to the 6.7% increase achieved with 2 wt% refined SWCNT + 2 wt% carbon black.

[0073] The unique performance characteristics previously observed in LiB energy cells are repeated in LiB power cells, where an increase in cell capacity is again accompanied by a simultaneous decrease in cell ESR. As illustrated in the impedance plot of Fig. 6, the greatest reduction at -3% cell impedance was achieved with a cathode formulation of 2 wt% purified SWCNT and carbon black, which also provided the highest gain in cell capacity. Similarly, cells with a cathode containing 3 wt% purified SWCNT and 3 wt% carbon black and 4 wt% purified SWCNT also exhibited lower ESR, but not to the same extent as cells with 2 wt% purified SWCNT and 2 wt% carbon black.

[0074] In addition to exhibiting excellent capacitance and impedance characteristics, the discharge rate performance of the LiB power cell containing refined SWCNT additive at increasing high currents was significantly improved compared to the standard cell. Figure 7 shows the favorable high-current discharge performance characteristics of a LiB cell with 2 wt% refined SWCNT + 2 wt% carbon black. This cell showed a 50% increase in capacity compared to the standard carbon black cell at a high discharge current of 20 A with significantly smaller capacity fade.

[0075] The results of comparing discharge curves between LiB power cells at a discharge current of 20A are shown in Fig. 8. Improved high-current performance of LiB power cells containing refined SWCNT additives was observed in cells with 2 wt% refined SWCNT + 2 wt% carbon black or 3 wt% refined SWCNT + 3 wt% carbon black. Specifically, the most improved 20A discharge performance from LiB power cells was achieved at a lower total conductive carbon content (4 wt% vs. 6 wt%).

[0076] When comparing the 20A discharge rate behavior of LiB cells assembled from two grades of SWCNT additives (purified and incorporated SWCNT), a performance difference is shown as illustrated in Fig. 9. The power cell incorporating purified SWCNT as an additive (light gray profile) exhibited superior high current discharge rate capability compared to the LiB cell with incorporated SWCNT additive (dark profile).

[0077] Comparative lifecycle data of the LiB power cell are shown in Fig. 10. Compared to a standard control cell containing 6 wt% carbon black, the initial increased capacity of the cell containing 2 wt% refined SWCNT additive + 2 wt% carbon black was maintained even after nearly 1,000 cycles at high current.

[0078] Figure 11 compares the initial lifecycle behavior of LiB cells assembled with two grades of SWCNT additives. The results show that, compared to a cell with SWCNTs purified with a conductive additive (solid symbol), a power cell incorporating SWCNTs with a conductive additive (open symbol) exhibits faster capacity fade after a given number of cycles.

[0079] Example 7 . Improved performance of LiB energy and power cells with respect to charge capacity, discharge capacity, and cell impedance when SWCNT is included as a conductive additive

[0080] FIG. 12 summarizes the results of Examples 1-6. In each of the two categories of power cells and energy cells, the cell showing the best performance with respect to charge capacity, discharge capacity, and impedance is a star ( Indicated by the symbol ). Adding purified SWCNT to the cathode formulation of a Li-ion battery cell in the described amount enables improved performance characteristics, such as increased cell capacity and simultaneously reduced or similar cell impedance, compared to cells using conventional carbon black conductive additives. These significant performance gains are realized at a lower total conductive additive content than is typical for cells with standard carbon black additives, thus allowing for an increase in the amount of active material in the electrode formulation, which has the potential to further increase LiB cell capacity. The enhanced performance of LiB cells with purified SWCNT additives is maintained during life cycle testing. Furthermore, these significant gains in LiB performance depend on the purity level of the SWCNT, as higher purity of the SWCNT additive leads to greater performance gains in LiB cells.

[0081] Example 8. Comparison of Specific Energy and Power Density of LiB Power Cells

[0082] The nominal battery energy per unit mass is called specific energy or gravimetric energy density. Specific energy is a characteristic of the LiB chemistry and packaging and is calculated by dividing the battery energy in Wh (watt-hours) by the mass (kg) of the packaged cell. Similarly, specific power or gravimetric power density is the maximum available power per unit mass of the battery and is calculated by dividing the battery power in W (watts) by the mass (kg) of the packaged cell.

[0083] The performance data summarized in Table 3 quantifies the dual gains in specific energy density and specific power density of LiB power cells achieved by incorporating purified SWCNTs into standard LiB cells containing only carbon black as a conductive additive. The values ​​in the table are provided for the comparison of cells with and without SWCNT additives, and the absolute values ​​vary depending on the cell design and active material used.

[0084] Table 3 Summary of performance data of a standard LiB cell compared to a cell containing purified SWCNTs. Standard LiB cell (6wt% carbon black) Current (ampere) Energy (Wh / kg) Electricity (W / kg) 1 126.7 87.0 2 122.7 173.1 4 118.1 344.2 10 107.7 846.5 20 81.9 1640.2 4wt% purified SWCNT LiB cell Current (ampere) Energy (Wh / kg) Electricity (W / kg) 1 137.8 89.4 2 132.8 178.8 4 125.7 355.2 10 113.3 872.6 20 99.6 1698.9 2wt% purified SWCNT + 2wt% SP LiB cell Current (ampere) Energy (Wh / kg) Electricity (W / kg) 1 145.4 89.0 2 141.5 177.2 4 137.3 352.3 10 130.6 867.3 20 119.8 1689.3 3wt% purified SWCNT + 3wt% SP LiB cell Current (ampere) Wh / kg W / kg 1 136.4 90.1 2 131.9 179.5 4 127.5 356.8 10 119.9 878.5 20 108.1 1712.8

[0085] As shown in Table 4, an increase in average cell performance was observed in all formulations containing purified SWCNT. The improvement in specific energy ranged from 22% to 46%, with a maximum increase in 2wt% SWCNT + 2wt% carbon black. At high C-rates, the improvement in specific power was between 3% and 4.4%, with a maximum increase observed in 3wt% SWCNT + 3wt% carbon black.

[0086] Table 4. Specific energy and power gains for refined SWCNTs versus standard LiB cells. LiB build % gain for specific energy versus standard cell (@ 20A) % gain for non-power vs. standard cell (@ 20A) Standard Cell (POR) --- --- 4 wt% SWCNT 22 3.6 2:2 (SWCNT:SP) (wt%) 46 3.0 3:3 (SWCNT:SP) (wt%) 32 4.4

[0087] Example 9. Comparison of performance of accepted, purified, and highly purified SWCNTs as conductive additives in LiB power cells

[0088] 2 wt% SWCNT, referred to as highly purified SWCNT and purified to over 99 wt% (i.e., containing ≤ 1 wt% inorganic impurities), was also used as a conductive additive in the cathode of a LiB power cell along with 2 wt% SP. Figure 13 compares the initial lifecycle behavior of a LiB power cell with a cathode containing the highly purified SWCNT grade compared to two other investigated grades of SWCNT additives, namely accepted SWCNT and purified SWCNT. The cycling results show that the best performance of the LiB cell was achieved using highly purified SWCNT as an additive. After 400 consecutive cycles, the LiB cell containing the highly purified SWCNT additive exhibited capacity retention close to 90%, which was higher than that achieved with the purified SWCNT conductive additive or the accepted SWCNT conductive additive.

[0089] As shown in Fig. 14, a comparison of the 20A discharge rate behavior of LiB cells with cathodes containing two grades of SWCNT additives with reduced inorganic impurities, namely purified and highly purified SWCNTs, reveals a performance difference. The high-rate performance results reflect cycling performance and show that the LiB power cell incorporating highly purified SWCNTs as an additive exhibits the highest current discharge rate capability, which is superior to that of a similar LiB power cell using purified SWCNTs as an additive.

[0090] Example 10 . Performance comparison of MWCNT vs. SWCNT as conductive additives in LiB power cells

[0091] The use of 2 wt% MWCNT as a conductive additive along with 2 wt% SP in the cathode of a LiB power cell was investigated to compare the efficiency of various CNT types as conductive additives. Figure 15 compares the initial lifecycle behavior of LiB cells assembled with MWCNT additives with individual cells containing three grades of SWCNT additives: accepted SWCNT, purified SWCNT, and highly purified SWCNT. The results show that the LiB power cell incorporating accepted MWCNT as an additive (dotted line) exhibited the fastest fade in capacity after initial cycling, maintaining < 85% capacity after 400 cycles, compared to cells with the three different grades of SWCNT, all of which showed superior cycling performance compared to cells containing MWCNT as an additive.

[0092] Figure 16 compares the 20A discharge rate behavior of a LiB power cell with a cathode containing an additive with the corresponding high-current discharge curves of cells containing various grades of SWCNT as additives. The power cell incorporating MWCNT as an additive exhibited the lowest high-current discharge rate performance and was inferior to similar LiB cells containing all grades of SWCNT additives.

[0093] Although some embodiments of the present invention have been described in the given embodiments, those skilled in the art will understand that various modifications can be made without departing from the scope of the invention. Accordingly, other embodiments are within the scope of the following claims.

Claims

Claim 1 A lithium-ion battery cell having a cathode comprising about 1-5 wt% of single-walled carbon nanotubes (SWCNT) as an active material and a conductive additive, wherein the SWCNT has an inorganic impurity content of 1 wt% or less, and the SWCNT is about 1300 m 2 A lithium-ion battery cell having a BET specific surface area of ​​ / g, wherein incorporating the SWCNT into the cathode provides increased capacity, the cathode further comprises carbon black as a second conductive additive, the combined content of SWCNT and carbon black in the cathode is 4 wt% to 6 wt%, and the weight ratio of SWCNT to carbon black is 1:

1. Claim 2 A lithium-ion battery cell according to claim 1, wherein the active material is selected from the group consisting of Li-NiMnCo-Oxide (NMC), Li-NiCoAl-Oxide (NCA), Li-Fe-Phosphate (LFP), Li-Cobalt-Oxide (LCO), Li-Manganese-Oxide (LMO), and any combination thereof. Claim 3 A lithium-ion battery cell according to claim 1, wherein the SWCNT in the cathode is 3 wt% and the carbon black is 3 wt%. Claim 4 A lithium-ion battery cell according to claim 1, wherein the SWCNT in the cathode is 2 wt% and the carbon black is 2 wt%. Claim 5 A lithium-ion battery cell according to claim 1, wherein the cell is a power cell, the amount of SWCNT is 2 to 3 weight%, and the amount of carbon black is 2 to 3 weight%. Claim 6 A lithium-ion battery cell according to claim 1, wherein the cell is a power cell, has an anode comprising graphite powder, carbon black as a conductive additive, a gelling agent, and a binder, and has LiPF6 as an electrolyte. Claim 7 A lithium-ion battery cell according to claim 1, wherein the cell is an energy cell and the combined content of SWCNT and carbon black in the cathode is 4 weight%. Claim 8 A lithium-ion battery cell according to claim 7, having an anode comprising graphite powder, carbon black as a conductive additive, a gelling agent, and a binder, and having LiPF6 as an electrolyte. Claim 9 A lithium-ion battery cell according to claim 1, wherein the SWCNT has a Raman G / D integrated peak area ratio of at least 20 measured using a laser having a wavelength of 532 nm. Claim 10 delete Claim 11 delete Claim 12 delete Claim 13 delete Claim 14 delete Claim 15 delete Claim 16 delete Claim 17 delete Claim 18 delete Claim 19 delete Claim 20 delete

Citation Information

Patent Citations

  • Novel electrode slice and preparation method thereof, and solid-state battery equipped with the same

    CN109713218A

  • Composition, preparation method and application of composition in lithium ion battery positive electrode material

    CN109904412A

  • Aligned single-walled carbon nanotube bulk structure and its production method

    JP2010159209A